RESTORATION OF CHILDREN’S HEALTH THROUGH PHYSICAL EDUCATION - Bekov Bek (Galaxy International Interdisciplinary Research Journal, 2023)
The article presents the results of a pedagogical experiment with children of the preparatory group of preschool educational institutions, at the stage of preparation for school.